Ending with Hope: A Resource for Closing Congregations - Gaede, Beth Ann (Rowman & Littlefield Publishers, 2002)
Why is it we do funerals so well but often balk at even recognizing the death of a congregation? Couldn’t we do grief ministry and funerals as well for social groups as we do for individuals?" challenges Gilson Waldkoenig, in his seminary classes. Waldkoenig, associate professor of church in society at Lutheran Theological Seminary at Gettysburg, contributes his special insights on the subject of church endings, in this unique and important book. Ending with Hope grows out of the understanding that although closing a congregation is in many ways about dying, it can also be about new life. Closing a congregation does not have to be about failure but can be about redirecting resources for new ministry. Contributors represent eight denominations and include more than a dozen pastors, lay leaders, judicatory staff, and others who have "been there"—who have helped congregations through the painful closing process. Resources include models for assessing whether a congregation should close; reflections on members’ and pastors’ experiences during closing; case studies; guidance for deciding what to do with a building; suggestions for selecting and preserving documents and artifacts; rituals for healthy closings; a survey of historical trends regarding closings; and other helpful materials.